Saving New Sounds Podcast Preservation and Historiography - Wade, Jeremy; Hoyt, Eric (University of Michigan Press, 2021)
"Over seventy-five million Americans listen to podcasts every month, and the average weekly listener spends over six hours tuning into podcasts from the more than thirty million podcast episodes currently available. Yet despite the excitement over podcasting, the sounds of podcasting's nascent history are vulnerable and they remain mystifyingly difficult to research and preserve. Podcast feeds end abruptly, cease to be maintained, or become housed in proprietary databases, which are difficult to search with any rigor. Podcasts might seem to be highly available everywhere, but it's necessary to preserve and analyze these resources now, or scholars will find themselves writing, researching, and thinking about a past they can't fully see or hear. This collection gathers the expertise of leading and emerging scholars in podcasting and digital audio in order to take stock of podcasting's recent history and imagine future directions for the format. Essays trace some of the less amplified histories of the format and offer discussions of some of the hurdles podcasting faces nearly twenty years into its existence. Using their experiences building and using the PodcastRE database-one of the largest publicly accessible databases for searching and researching podcasts-the volume editors and contributors reflect on how they, as media historians and cultural researchers, can best preserve podcasting's booming audio cultures and the countless voices and perspectives podcasting adds to our collective soundscape."